Applicability of Statistical Process Control for Flotation of Metals Complex - Vapur, Huseyin (Asian Journal of Chemistry, 2010)
Statistical process control (SPC) can be assisted flotation plants to obtain good quality and standard products. The aims of this study was the determination of the lower control limit (LCL), upper control limits (UCL) and process capability indexes (CP) of the results for complex lead-zinc ores obtained from Beroner Mining Co. in North-Eastern of Turkey. The statistical determinations with moving range (MR) method were used for showing differences between in the quality of the concentrates and recovery ratios. The variability of grade values relative to contract specifications was compared with the tailings grades and recovery ratios. Afterwards, the variation in the revenue of the lead-zinc producer resulting from the premium or penalty application was analyzed. The weaknesses of flotation plant were determined and operational solutions to minimise unwanted anomalies or fluctuations for grades of concentrate and grades of tailings were fixed to find optimum products.